Does night-time aircraft noise trigger mortality? A case-crossover study on 24 886 cardiovascular deaths. (30th November 2020) - Saucy, Apolline; Schäffer, Beat; Tangermann, Louise; Vienneau, Danielle; Wunderli, Jean-Marc; Röösli, Martin
Abstract: Aims: It is unclear whether night-time noise events, including from aeroplanes, could trigger a cardiovascular death. In this study, we investigate the potential acute effects of aircraft noise on mortality and the specific role of different night-time exposure windows by means of a case-crossover study design. Methods and results: We selected 24 886 cases of death from cardiovascular disease (CVD) from the Swiss National Cohort around Zürich Airport between 2000 and 2015. For night-time deaths, exposure levels 2 h preceding death were significantly associated with mortality for all causes of CVD [OR = 1.44 (1.03–2.04) for the highest exposure group (LAeq > 50 dB vs. <20 dB)]. Most consistent associations were observed for ischaemic heart diseases, myocardial infarction, heart failure, and arrhythmia. Association were more pronounced for females ( P  = 0.02) and for people living in areas with low road and railway background noise ( P  = 0.01) and in buildings constructed before 1970 ( P  = 0.36). We calculated a population attributable fraction of 3% in our study population. Conclusion: Our findings suggest that night-time aircraft noise can trigger acute cardiovascular mortality. The association was similar to that previously observed for long-term aircraft noise exposure. Graphical Abstract: